An analytical method for the meshing characteristics of asymmetric helical gears with tooth modifications. (July 2023) - Mo, Shuai; Li, Yuhua; Wang, Dongdong; Hu, Xiaosong; Bao, Heyun; Cen, Guojian; Huang, Yunsheng
Highlights: The improved analytical method for the time-varying meshing stiffness model. The meshing characteristics of asymmetric helical gears. The coupling effect of gear body part on helical gears. Abstract: This paper establishes a time-varying meshing stiffness (TVMS) analytical method for asymmetric helical gear pairs based on the potential energy principle and slice method. The method considers the adjacent teeth' influence on the deformation of the gear body part. The proposed method is verified the reasonableness by finite element (FE) analysis. The basic parameters of asymmetric helical gear such as helical angle, pressure angle and tooth width are estimated for the meshing characteristics. The results show that the increase of helix angle, pressure angle of the driving side, normal modulus and tooth width will affect the contact ratio and maximum meshing stiffness of helical gears. The variation of these parameters can minimize the fluctuation of the TVMS curve when the overlap contact ratio reaches an integer. The variation trend of the loaded-static transmission error (LSTE) is opposite to that of the TVMS curve. The load share ratio (LSR) on a pair of gear pairs will decrease with the increase of the degree of reattachment. Furthermore, the influence of tooth modifications on TVMS is estimated by using the proposed method. The mean value of stiffness is reduced after the tooth modifications. The TVMS curve changes more gently after the tooth tip modification.